渐开线凸轮误差对齿形精度影响的分析 - 王启明; 马勇; 李克洪; 娄志峰 (Jixie chuandong)
Involute cam is an important attachment which produce involute profile in the copying gear grinder; the accuracy of which directly decide the profile accuracy of gear which is grinded. The mathematical model of the influence about involve cam error to profile precision is established by means of the operation principle of the copying gear grinder; the relevant solution is proposed, which provide some theoretical foundation for accurate adjusting machine tool.